American Publishers, Protesters, and Travelers Under Surveillance. - Hundley, Rachel (Humanist)
Presents an article on the efforts of the U.S. government in preventing terrorism. Discussion on the warning given by the Treasury Department to publishers on editing of manuscripts from nations under the trade embargos; Information no the counter-terrorism computer system introduced by the Homeland Security for federal, state and local intelligence and law enforcement agencies; Plans of the Transportation Security Agency to have airlines report to the government the travel activities of citizens who travel abroad.